The efficacy of conversion from IUI to IVF-ET in infertility patients with hyper-response to ovulation induction: a retrospective study - Zhong, Yiping; Li, Jin; Ying, Ying; Wu, Haitao; Zhou, Canquan; Xu, Yanwen; Wang, Qiong; Li, Jie; Shen, Xiaoting (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2012)
BACKGROUND: The aim of the study was to determine the efficacy of in vitro fertilization and embryo transfer (IVF-ET) in patients with hyper-response to ovulation induction for intrauterine insemination (IUI). METHODS: Patients with polycystic ovary syndrome (PCOS) who were initially treated with IUI in our centre between Jan 2007 and Oct 2010 were retrospectively analyzed. The ovarian hyper-stimulation syndrome (OHSS) found in 50 patients was then treated with IVF-ET following informed consent. RESULTS: The fresh transfer had 42 cycles and a total of 87 embryos were transferred. Urine pregnancy tests were positive in 15 patients and fetal heart beat was detected in 12 patients by transvaginal ultrasound, from which 3 patients had two fetuses, 2 patients had three fetuses, and 7 patients had a single fetus. The overall clinical pregnancy rate was 28.5% (12/42) for the fresh embryo transfer. A total of 21 cycles of frozen embryo transfer with up to 55 embryos were conducted for patients who were not pregnant at the end of fresh embryo transfer cycles or who did not receive fresh embryo transfer in the first place. Urine pregnancy tests were positive in 10 patients and fetal heart beat was detected in 8 patients. The clinical pregnancy rate was 38.1% (8/21) for frozen embryo transfer. CONCLUSION: We conclude that IVF-ET is an effective method for patients with hyper-response to ovulation induction in IUI.
Keywords: fertilizace in vitro; Embryo Transfer; Humans; přenos embrya; Female; lidé; ženské pohlaví; ženská infertilita; ovariální hyperstimulační syndrom; těhotenství; Ovulation Induction; Insemination, Artificial; Infertility, Female; dospělí; umělá inseminace; indukce ovulace; Adult; Pregnancy; Fertilization in Vitro; Ovarian Hyperstimulation Syndrome